Musicking and Identities in and from Religious Places of Thai Diasporas in Chicagoland - Werstler, Matthew (Journal of Urban Culture Research, 2025)
Thai Americans are constantly imagining, sustaining, and performing their Thai identity to varying degrees, and this can be seen in the Chicagoland area. Regardless of the differences in musical genre or form, Thai diaspora communities perform and negotiate identity within sacred spaces through musicking. The act of musicking is important for Thai Americans to share their life with one another. With the onset of the Covid-19 Pandemic, Thai musicking communities of religious spaces in the Chicagoland area turned to virtual and outdoor mediums to perform and create. While changes were needed so that musicking opportunities could continue during the pandemic, the fluidity of space is not a new concept; the Thai musicking communities in Chicagoland were creating outside of their designated spaces, even prior to the pandemic. The identity of who they are and the religious spaces from which they come, remain a part of the performances, even as they create beyond those sacred spaces.